Ca2+ signaling and lipid transfer ‘pas a deux’ at ER-PM contact sites orchestrate cell migration - Khaled Machaca (194372) (2020)
Contact sites between the endoplasmic reticulum (ER) and plasma membrane (PM) regulate both non-vesicular lipid transfer as well as Ca2+ signaling with multiple interactions between the two pathways. Here I discuss recent findings that offer exciting insights into the role of store-operated Ca2+ entry (SOCE), Oxysterol-binding protein (OSBP)-related proteins ORP3, Arf5 and the Arf GEF IQSec1 in this crosstalk and how they regulate cell migration and focal adhesion disassembly. Other Information Published in: Cell Calcium License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ceca.2020.102226